2009
DOI: 10.1152/ajpregu.90608.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic and anaerobic metabolic inhibitors on avian intrapulmonary chemoreceptors

Abstract: Birds have rapidly responding respiratory chemoreceptors [intrapulmonary chemoreceptors (IPC)] that provide vagal sensory feedback about breathing pattern. IPC are exquisitely sensitive to CO(2) but are unaffected by hypoxia. IPC continue to respond to CO(2) during hypoxic and even anoxic conditions, suggesting that they may generate ATP needed for signal transduction anaerobically. To assess IPC energy metabolism, single-cell action potential discharge and acid-base status were recorded from 26 pentobarbital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We detected both highland and lowland sparrows had similar maximal LDH and CK activities, which means similar maximal velocity on lactate metabolism for both populations. There are two possible explanations: (1) highland sparrows are able to counter the adverse effect of anaerobic metabolism, which is more easily induced by hypoxic environment (Samaja et al 1997;Pilarski et al 2009), on acid-base equilibrium in cardiomyocytes via lower glycolysis level (Burggren and Cameron 1980;Casiday and Frey 2012;Hebisz et al 2016) ; (2) both population possessed similar maximal capacity on production and regeneration of ATP by lactate metabolism (Ingwall et al 1985;Kodde et al 2007), which indicate that the highland sparrows, compared to their lowland counterparts, could better cope with the extra demand of ATP when the cardiac workloads increased but the aerobic metabolism is suppressed. Since the leakage of LDH and CK into the cardiovascular system are documented as indexes of myocardial injury (Kaur et al 1997), our results showed that the cardiac functions of both the highland and lowland sparrows were unlikely to be injured.…”
Section: Discussionmentioning
confidence: 99%
“…We detected both highland and lowland sparrows had similar maximal LDH and CK activities, which means similar maximal velocity on lactate metabolism for both populations. There are two possible explanations: (1) highland sparrows are able to counter the adverse effect of anaerobic metabolism, which is more easily induced by hypoxic environment (Samaja et al 1997;Pilarski et al 2009), on acid-base equilibrium in cardiomyocytes via lower glycolysis level (Burggren and Cameron 1980;Casiday and Frey 2012;Hebisz et al 2016) ; (2) both population possessed similar maximal capacity on production and regeneration of ATP by lactate metabolism (Ingwall et al 1985;Kodde et al 2007), which indicate that the highland sparrows, compared to their lowland counterparts, could better cope with the extra demand of ATP when the cardiac workloads increased but the aerobic metabolism is suppressed. Since the leakage of LDH and CK into the cardiovascular system are documented as indexes of myocardial injury (Kaur et al 1997), our results showed that the cardiac functions of both the highland and lowland sparrows were unlikely to be injured.…”
Section: Discussionmentioning
confidence: 99%